The Impact of COVID-19 on Interpersonal Aspects in Elementary School - Herrmann, Lukas; Nielsen, Birgitte Lund; Aguilar-Raab, Corina (Frontiers in Education, 2021)
Social-emotional education and the relational competence of school staff and leaders are emphasized in research since they strongly impact childrens’ social, emotional, and cognitive development. In a longitudinal project—Empathie macht Schule (EmS)—we aim at evaluating the outcome and process of an empathy training for the whole school staff, including leaders. We compare three treatments to three control elementary schools via a mixed-methods approach employing qualitative and quantitative research methods targeting both, the school staff and the schoolchildren. Since the start of the project in 2019, the COVID-19 pandemic has disrupted the global education process, that is, the range of training activities for school staff in an unprecedented manner. First the lockdown and then the hygienic measures impact the habits and certainties in schools on multiple levels, including artifacts (e.g., physical distancing measures and virtual platforms), processes (e.g., virtual learning and home-schooling), social structures (e.g., separation of a high-risk group), and values (e.g., difficulties in building relations and showing empathy due to physical distance). Leaders and staff are facing an uncertain situation, while their actions and decisions may—also unintentionally—shape the social reality that will be inhabited to a significant extent. In this context, a number of questions become salient. How does the disruption of the pandemic affect interpersonal relationships, interactions, and the social field—the sum of relationships within the system of a school—as a whole? And specifically, how do the actors reflect on changes in the social field, their relationships, and the schools’ and classrooms’ overall relationship quality due to the crisis? The assessment combines qualitative interviews with leaders and teachers (N = 10) along with a self-report survey (N = 80) addressing the effects of the pandemic on interpersonal aspects in schools. Surprisingly, a number of positive effects were mentioned regarding the learning environment in the smaller-sized classes, which were caused by hygienic measures, as well as increased cohesion among faculty. The potential influence of these effects by consciously shaping relationships and cultivating empathy is discussed in the article.